Prediction and Classification Machine Learning Models in Diabetic Studies - Saroj , Rakesh Kumar; Yadav , Kanchan (Socio-Scientific Interaction in Diabetes and Cancer and Its Management, 2023)
Diabetes is one of the major health problems globally. Diabetes is a metabolic disorder that causes various complications such as stroke, chronic kidney disease, foot ulcer, retinopathy, diabetic ketoacidosis, and many more. Timely predictions and classifying of the diabetes problem will help to prevent diabetes. There is various machine-learning approach that can be used to predict and classify diabetes problem in the general population. The diabetes prediction and classification process can help to further improve the disease. This paper will discuss the machine learning applications and steps to understanding the concepts. The purpose of this paper framework is to early prediction and classification of diabetes to reduce stress and save human life, and financial burden.